Development of Social Sciences Teaching Materials Based on Local Wisdom: Needs Analysis for Middle School Social Sciences Teachers in South Bengkulu - Ririn Selvianti; Maryam Maryam; Yuhaswita Yuhaswita; Yeni Wulandari (UIN Fatmawati Sukarno Bengkulu, 2024)
Bengkulu has a lot of local wisdom which has great potential to be used as a source and learning material for social studies in junior high schools. However, due to the lack of available literature, social studies teachers in Bengkulu are hampered by integrating local wisdom in learning. This article aims to analyze the needs for developing social studies teaching materials based on Bengkulu local wisdom with two main focuses: 1) the need for teaching materials based on types of local wisdom; and 2) the need for teaching materials based on the type/form of teaching materials. This research was conducted on junior high school social studies teachers in South Bengkulu using descriptive qualitative methods. The data in this research were collected using in-depth interviews and open questionnaires and analyzed using an interactive model. The research results show that: 1) all social studies teachers in South Bengkulu strongly agree and feel it is necessary to develop social studies teaching materials based on local wisdom; 2) the types of local wisdom that most need to be developed are oral traditions, customs, rites, manuscripts and traditional knowledge (based on sources) and local wisdom for environmental preservation, morality and spirituality, disaster mitigation and conflict resolution and food security. Several types of local wisdom that are really needed by social studies teachers are based on considerations of the relevance of the material; 3) the type of teaching material that most needs to be developed is in the form of a module. Modules are much needed because they are considered more practical, making it easier for teachers to carry out the learning process.